2009
DOI: 10.1016/j.brainres.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in hippocampal astrocytes induced by environmental enrichment in mice

Abstract: Environmental enrichment is known to induce plastic changes in the brain, including morphological changes in hippocampal neurons, with increases in synaptic and spine densities. In recent years, the evidence for a role of astrocytes in regulating synaptic transmission and plasticity has increased, and it is likely that morphological and functional changes in astrocytes play an important role in brain plasticity. Our study was designed to evaluate changes in astrocytes induced by environmental enrichment in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 54 publications
2
64
0
2
Order By: Relevance
“…Thus, the LH paradigm induced increases in the number of activated and nonactivated astrocytes, which could be a compensatory response to stress. In support of this, environmental enrichment, which increases neurogenesis in the hippocampus, produced an increase in the ramification of astrocytic processes and the number and length of primary processes extending in the hippocampus (Viola et al, 2009). Furthermore, an increase in the number of GFAP-labeled astrocytes was seen in the cingulate of postpartum rats (Salmaso et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, the LH paradigm induced increases in the number of activated and nonactivated astrocytes, which could be a compensatory response to stress. In support of this, environmental enrichment, which increases neurogenesis in the hippocampus, produced an increase in the ramification of astrocytic processes and the number and length of primary processes extending in the hippocampus (Viola et al, 2009). Furthermore, an increase in the number of GFAP-labeled astrocytes was seen in the cingulate of postpartum rats (Salmaso et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
“…3). Reactive astrocytes are recognized by GFAP labeling and extended lengths of processes (Viola et al, 2009). We differentiated activated astrocytes from nonactivated astrocytes mainly by dimension rather than by length of longest process.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Regional densitometry is a measurement of absorbance generated by the NADPH-d reaction product, formazan, in all the tissues, including neurons, glia and fibers, while neuronal optical densitometry is the same measurement performed only in the neuronal cytoplasm Xavier et al 2005;Vaschenko and Kotsyuba 2008;Viola et al 2009). For this purpose, a Nikon-Eclipse E-600 microscope (500x; Japan) was employed together with Image Pro-Plus Software 6.0 (Media Cybernetics, USA).…”
Section: Optical Densitometrymentioning
confidence: 99%
“…The NADPH-d activity was evaluated using regional and neuronal semi-quantitative optical densitometry Xavier et al 2005;Vaschenko and Kotsyuba 2008;Viola et al 2009). Regional densitometry is a measurement of absorbance generated by the NADPH-d reaction product, formazan, in all the tissues, including neurons, glia and fibers, while neuronal optical densitometry is the same measurement performed only in the neuronal cytoplasm Xavier et al 2005;Vaschenko and Kotsyuba 2008;Viola et al 2009).…”
Section: Optical Densitometrymentioning
confidence: 99%
“…In this study, female Wistar rats in the EE condition showed significantly higher staining intensity and percent area of staining for astroglia in the CA1, but not CA3. While another study of male mice [43] found no change in immunoreactivity or density of astroglia following EE, it did report structural changes in the hippocampal CA1 following EE. In the motor cortex of adult female mice, EE has been shown to increase the number of astroglia [44].…”
Section: Discussionmentioning
confidence: 99%